Continuous renal replacement therapy in intensive care: When is the optimal timing? (Annals of Medical Research, 2023)
Aim: Acute kidney injury is one of the most widespread problems in critical patients in intensive care. It leads to severe morbidity and mortality. Although the indications for emergency dialysis are well known, the timing for initiating continuous renal replacement therapy (CRRT) in the critical patient is still unclear. The purpose of this study was to evaluate the effect on mortality of the timing of continuous renal replacement therapy in patients follow-up in intensive care and receiving renal replacement.Materials and Methods: Patients’ medical records were reviewed and analyzed retrospectively. Aged over 18, with no previously known chronic kidney disease, and receiving only CRRT was included in this study who were treated in intensive care over a one-year period. The patients were divided into two groups, an early group consisting of KDIGO stages 1 and 2, and a late group consisting of KDIGO stage 3. These were than evaluated in terms of 28-day mortality.Results: Forty-eight patients with a mean age of65.94±19.61 years were included in the study. Twenty-eight (58.3%) patients were men. Cardiovascular diseases were the most frequent diagnoses, in16 (33.3%) patients and comorbidity was detected in 32 (66.7%). SOFA, blood urea nitrogen, creatinine, and procalcitonin values differed between the groups, but no difference was observed in 28-day mortality.Conclusion: The study results showed that early or late application of CRRT has no positive effect on survival, but further randomized studies on the subject are now needed.
Keywords: Renal replacement therapy; Intensive care; Acute kidney injury; Timing